Effect of the Addition of Hydrofoil on Lift Force and Resistance in 60 M High-Speed Vessel - Ismail, Izzuddin Nadzir; Manik, Parlindungan; Indiaryanto, Mahendra (Kapal: Jurnal Ilmu Pengetahuan dan Teknologi Kelautan, 2020)
The development of sea transportation technology is needed to meet the demand for ships that can carry heavier loads and operate at high speeds. Modifications in the form of additional hydrofoil variations were conducted to produce higher lift and reduce the resistance generated by the ship so that the ship can go more efficiently at high speed. This study aims to obtain the effect of adding hydrofoil to ships with variations in the type and shape of foil and find out which types and shapes can reduce resistance on the ship. This research was conducted with several model analysis tests using Computational Fluid Dynamic (CFD) based software, namely Tdyn, at several different speeds. The results of this study show that of the six variation models analyzed, rectangular fully submerged foil models can reduce the total resistance value of the ship by 17.822% from the original ship on Froude Number (Fr) 0.670. The type and shape of the foil is very influential on the lift and resistance produced by the ship.